Intervals as musical fingerprints: perceptual and pedagogical insights—a scoping review - Kendüzler, Mustafa (Frontiers in Psychology, 2026)
The perception and training of musical intervals form a central foundation for pitch cognition and musical understanding within solfege education. This scoping review maps the existing literature on interval training, emphasizing the interplay between perceptual mechanisms, pedagogical modeling, and instructional design. Following the PRISMA-ScR guidelines, systematic searches were conducted across three academic platforms—ERIC, Google Scholar, and JSTOR—using combinations of the keywords “interval training,” “solfege,” “pitch perception,” and “music education.” Thirty-five peer-reviewed studies published between 2010 and 2025 were analyzed, while historical and theoretical sources (1889–2009) were also considered to contextualize the pedagogical and cognitive development of interval training. Thematic synthesis identified three overarching domains: (1) perceptual-cognitive mechanisms underlying interval recognition, tonal awareness, and auditory feedback; (2) pedagogical models integrating auditory, visual, and kinesthetic modalities in solfege instruction; and (3) instructional frameworks promoting pitch stability, long-term learning, and vocal-motor integration. Collectively, the reviewed evidence suggests that structured interval training enhances pitch discrimination, strengthens the mapping between perception and vocal production, and provides a sustainable foundation for music learning. By linking perceptual cognition with pedagogical practice, this study contributes to a broader understanding of how interval-based training supports both the psychological and educational dimensions of musical development.